Biogas from slaughter house waste and optimization of the process - Rouf, MA; Islam, MS; Rabeya, T; Mondal, AK; Khanam, M; Samadder, PR; Ara, Y (Bangladesh Journal of Scientific and Industrial Research, 2016)
To assess the potential of biogas generation by anaerobic digestion from slaughter house waste (undigested stomach content) and to determine the optimum conditions for biogas generation from the substrate, different proportions of substrate were used in six batch reactors R1, R2, R3, R4, R5 and R6. The reactors were operated with initial volatile solid concentrations of 34.00, 50.80, 67.20, 51.60, 48.10 and 63.36 g/l and corresponding specific gas production obtained was 0.258, 0.200, 0.160, 0.270, 0.201 and 0.170 l/g respectively. The volatile solids (VS) destruction efficiency was 31.71%, 29.15%, 28.26%, 32.29%, 30.56 and 29.08% as well as chemical oxygen demand (COD) reduction achieved in the test reactors were 40.31%, 44.44%, 49.40%, 53.24%, 48.55% and 51.26% in R1, R2, R3, R4, R5 and R6 respectively. Methane yield in different reactors varied from 72% to 76%. The optimum mix for generation of biogas from the substrate was 75% slaughter waste mixed with 25% cow dung. Bangladesh J. Sci. Ind. Res. 51(3), 203-214, 2016